2009
DOI: 10.1089/end.2008.0266
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Ureteral Reimplantation: A Single Center Experience and Literature Review

Abstract: Laparoscopic reconstructive surgery for managing benign distal ureteral strictures is both safe and effective. Although open surgery currently remains the gold standard for these patients, all operative steps can be replicated laparoscopically, and this may become the future standard treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 10 publications
1
21
0
3
Order By: Relevance
“…Although ORT was longer initially, with growing experience there was an improvement in our ORT (mean 212 min, range 170-310 min) [19,21,22,23,24,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Although ORT was longer initially, with growing experience there was an improvement in our ORT (mean 212 min, range 170-310 min) [19,21,22,23,24,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…[3,[6][7][8][9][10][11][12][13][14][15][16][17] Rassweiler et al [7] observed longer operative time (253 minutes vs. 220 minutes), shorter hospital stay (8 days vs.17 day) with 100% successs rate in the [11] 1 210 3 90 50 mg morphine…”
Section: Discussionmentioning
confidence: 99%
“…a distal stump of more than 1 cm, has not been previously described in the literature because, in most cases, a ureteral re-implantation has been performed when there is no portion of the distal ureter that is large enough for end-to-end anastomosis. 2,3,9 Intramural ureter dissection using a ureteral stent for guidance is simple and straightforward; we can collect up to 1 cm of viable and healthy distal ureter, facilitating endto-end anastomosis. Our technique also reduces morbidity and surgical time compared to other techniques, including direct re-implantation of the ureter into the bladder, 2,3,10 and eliminates the need for an anti-reflux mechanism.…”
Section: Discussionmentioning
confidence: 99%